Small intestinal bacterial overgrowth: duodenal aspiration vs glucose breath test - Erdogan, A.; Rao, S. S. C.; Gulley, D.; Jacobs, C.; Lee, Y. Y.; Badger, C. (Neurogastroenterology and motility, 2015)
Background The diagnosis of small intestinal bacterial overgrowth (SIBO) remains challenging. Our aim was to examine the diagnostic yield of duodenal aspiration/culture and glucose breath test (GBT), and effects of gender, race and demographics on prevalence of SIBO. Methods Patients with unexplained gas, bloating and diarrhea and negative endoscopy, imaging and blood tests were prospectively enrolled in two centers in USA. Randomly, within 1 week each patient underwent both duodenal aspiration/culture and GBT. The diagnostic yield of each test and relationship of symptoms, and effects of ethnicity, age, and gender on prevalence of SIBO were assessed and compared. Key Results Duodenal culture was positive in 62/139 (44.6%) subjects and GBT was positive in 38/139 (27.3%) subjects with an overall diagnostic agreement of 65.5%. The sensitivity, specificity, positive and negative predictive value of GBT was 42%, 84%, 68%, and 64%, respectively. Ethnicity or gender did not influence SIBO, but SIBO positive patients were older (p = 0.0018). Symptom patterns were similar except bloating was more prevalent in GBT positive and gas in culture positive subjects. Conclusions & Inferences Duodenal aspiration/culture identifies 45% of patients with suspected SIBO. GBT has lower sensitivity but good specificity for detection of SIBO. There were no ethnic or gender differences in the prevalence of SIBO, but patients with SIBO were older. Because GBT is non‐invasive, it should be considered first in patients with suspected SIBO. The diagnosis of small intestinal bacterial overgrowth (SIBO) remains challenging.